Effect Of Varying Rates Of Organic Amendments On Porosity And Infiltration Rate Of Sandy Loam Soil - Essien, OE (Journal of Agriculture and Environment, 2013)
Infiltration rate and porosity of sandy loam soil amended separately with goatyard manure (GYM) and poultry waste at 30, 50 and 70 tonnes/hectare each were investigated and the results were statistically analyzed using SPSS ver 17 package. Infiltration rates under GYM amendment and poultry waste amendment showed significant difference (p?0.01), indicating that the variation of infiltration under GYM amendment was superior to the use of poultry waste. Infiltration rates under poultry waste amendment and those of the control soil correlated perfectly (r= 0.99, p?0 .01). The application of 70t/ha of GYM indicated no superior short-term effect on soil’s infiltration rate than its lower amendment rates. The constant infiltration rate of amended soil under 30T/ha of GYM was reduced to 1.60cm/min below the 2.28cm/min for its GYM counterpart and 1.69cm/min for the control soil; and is recommended for optimum irrigation water conservation in sandy loam soil. The change in porosity was less under GYM amendment than under poultry waste amendment. The Journal of Agriculture and Environment Vol:12, Jun.2011, Page 51-58 DOI: http://dx.doi.org/10.3126/aej.v12i0.7563